Gas sensor using surface plasmon resonance, a simulations-based study (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
The propagating surface plasmons are collective oscillations of the electrons present on metallic film surfaces, with which it is possible to couple light from an incident beam. In the following work, we present a simulation-supported theoretical review of the physical foundations of surface plasmon resonance using Dielectric/Au film/Dielectric or Dielectric/Ag film/Dielectric systems. We study the possibilities of implementing a gas sensor using these two types of structures.